Ammonia stress-induced heat shock factor 1 enhances white spot syndrome virus infection by targeting the interferon-like system in shrimp - Xin-Xin Wang; Hui Zhang; Jie Gao; Xian-Wei Wang (mBio, 2024)
ABSTRACT Disease emergence is the consequence of host-pathogen-environment interactions. Ammonia is a key stress factor in aquatic environments that usually increases the risk of pathogenic diseases in aquatic animals. However, the molecular regulatory mechanisms underlying the enhancement of viral infection following ammonia stress remain largely unknown. Here, we found that ammonia stress enhances white spot syndrome virus infection in kuruma shrimp (Marsupenaeus japonicus) by targeting the antiviral interferon-like system through heat shock factor 1 (Hsf1). Hsf1 is an ammonia-induced transcription factor. It regulates the expression of Cactus and Socs2, which encode negative regulators of NF-κB signaling and Jak/Stat signaling, respectively. By inhibiting these two pathways, ammonia-induced Hsf1 suppressed the production and function of MjVago-L, an arthropod interferon analog. Therefore, this study revealed that Hsf1 is a central regulator of suppressed antiviral immunity after ammonia stress and provides new insights into the molecular regulation of immunity in stressful environments.IMPORTANCEAmmonia is the end product of protein catabolism and is derived from feces and unconsumed foods. It threatens the health and growth of aquatic animals. In this study, we demonstrated that ammonia stress suppresses shrimp antiviral immunity by targeting the shrimp interferon-like system and that heat shock factor 1 (Hsf1) is a central regulator of this process. When shrimp are stressed by ammonia, they activate Hsf1 for stress relief and well-being. Hsf1 upregulates the expression of negative regulators that inhibit the production and function of interferon analogs in shrimp, thereby enhancing white spot syndrome viral infection. Therefore, this study, from a molecular perspective, explains the problem in the aquaculture industry that animals living in stressed environments are more susceptible to pathogens than those living in unstressed conditions. Moreover, this study provides new insights into the side effects of heat shock responses and highlights the complexity of achieving cellular homeostasis under stressful conditions.